Angiokeratoma Of the Vulva In A Young Woman - Joshi Arun; Sah Shatrughan P; Agrawal Sudha; Agarwalla Arun (Wolters Kluwer Medknow Publications, 1999)
A 34 year old female had vascular, keratotic papules on her external genitalia for 4 years. The histopathology was diagnostic of angiokeratoma. The case is being reported because of its uncommon occurrence.